Meningkatkan Kemampuan Pemahaman Konsep Matematika Melalui Model Pembelajaran Realistic Mathematics Education Menggunakan Alat Peraga Kubus dan Balok - Nurain A Hubulo; Evi Hulukati; Hamzah B. Uno; Taulia Damayanti (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
The purpose of this study was to improve the understanding of mathematical concepts of students through Realistic Mathematics Education. Learning model assisted by teaching aids on cube and block material. This research is classroom action research. The research subjects were class VIIIA students for the 2021/2022 academic year with 26 people. The techniques used in data collection are observation and tests. The data analysis technique in this study is data analysis of teacher observations, student observations and tests of understanding mathematical concepts. The research procedure includes planning, implementation, observation, and reflection. The study consisted of 2 cycles. Realistic Mathematics Education learning assisted by teaching aids on cube and block material, as long as this research has been running according to the learning implementation plan, has succeeded in creating a conducive learning situation, and increasing students' understanding of concepts. The results showed that the ability to understand mathematical concepts in the first cycle was 50% less criteria, and in the second cycle, 81% good criteria. The results of observations of teachers' teaching skills when managing learning has increased. In the first cycle, it reached 69.12% good criteria, while the second cycle reached 85.28% excellent criteria. The results of observations of student learning activities have increased. From the first cycle, the percentage is 63.75 good criteria, while the second cycle is 83.75% excellent criteria.